Challenges and Dilemmas of Civil Society movements in India. Issue 2 (14th June 2019) - Pulla, Venkat; Jaysawal, Neelmani; Saha, Sudeshna
Abstract: Civil Society spaces provide citizens opportunities to frame their collective identities and interests through the formation of voluntary interest groups and organisations set to specific purposes. In the west, historically these interest groups have contributed to the development of political thought that assisted to forge the economic interests of emerging bourgeoisie. This paper situated in the context of India begins with a thematic perspective and reviews the challenges that emerge as a result of the demands that emerge within the civil society space. The paper considered three broad range organizations for this review such as the Narmada Bachao Andolan (Save the river Narmada Campaign); National Alliance for People's Movement (NAPM); and the Self‐Employed Women's Association (SEWA). The authors see civil society as a conciliating place—where individual interests appear to mingle with societal requirements while providing adequate representation to the marginalized groups and expression of concerns around economic and environmental rights.